The Function of the NMDA Receptor in Hypoxic-Ischemic Encephalopathy - Zhang, Xiaotong; Peng, Kaizhen; Zhang, Xiaomin (Frontiers in Neuroscience, 2020)
Hypoxic-ischemic encephalopathy (HIE) is one of the main forms of neonatal brain injury which could lead to neonatal disability or even cause neonatal death. Therefore, HIE strongly affects the health of newborns and brings heavy burden to the family and society. It has been well studied that N-methyl-D-aspartate (NMDA) receptors are involved in the excitotoxicity induced by hypoxia ischemia in adult brain. Recently, it has been shown that the NMDA receptor also plays important roles in HIE. In the present review, we made a summary of the molecular mechanism of NMDA receptor in the pathological process of HIE, focusing on the distinct role of GluN2A- and GluN2B-containing NMDA receptor subtypes and aiming to provide some insights into the clinical treatment and drug development of HIE.